Factors influencing adoption of environment management practices among Malaysian logistics companies / Irwan Ibrahim - Ibrahim, Irwan (2017)
With increasing awareness of environmental issues among business owner, there has been rising demand for developing environmentally responsible and friendly business operations However, it has been reported that despite business owner aware of the negative impacts towards the environment from their business operations, the level of implementation of environmental-friendly practices is low. Thus, this research seeks to examine the adoption of an environmental management practices (EMP) in Malaysia logistics industry and identify the key factors that contribute to successful adoption. Using the extended theory of Technological-Organizational-Environmental framework, data were collected through questionnaire survey conducted among Malaysia logistic service providers, and 205 samples were analyzed. The data was input into SPSS and analyzed used Structural Equation Modeling to test the research hypotheses and the model that has high reliability and validity is developed. Amos results indicate that technological and environmental factors have significantly positive influences on environmental management practices adoption. However, the influences of environmental factors is not significant on environmental management practices adoption. The findings are based on a single-country and single-industry study, so the current research may be limited in its generalizability. The findings of this paper are original, as no other similar empirical study in analyzing the adoption of EMP in the logistics industry, especially for Malaysia's logistics industry. Owing to the lack of empirical research on the adoption of EMP in Malaysia, this research provides an empirical study on the factors influencing the adoption of EMP by logistics service providers in Malaysia. This research results can help Malaysia's logistics companies develop better strategies to adopt EMP, and can make them become environmentally responsible and friendly logistics service providers.